Mutation p.R356Q in the Collybistin Phosphoinositide Binding Site Is Associated With Mild Intellectual Disability - Chiou, Tzu-Ting; Long, Philip; Schumann-Gillett, Alexandra; Kanamarlapudi, Venkateswarlu; Haas, Stefan A.; Harvey, Kirsten; O’Mara, Megan L.; De Blas, Angel L.; Kalscheuer, Vera M.; Harvey, Robert J. (Frontiers in Molecular Neuroscience, 2019)
The recruitment of inhibitory GABA-A receptors to neuronal synapses requires a complex interplay between receptors, neuroligins, the scaffolding protein gephyrin and the GDP-GTP exchange factor collybistin. Collybistin is regulated by protein-protein interactions at the N-terminal SH3 domain, which can bind neuroligins 2/4 and the GABA-AR α2 subunit. Collybistin also harbours a RhoGEF domain which mediates interactions with gephyrin and catalyses GDP-GTP exchange on Cdc42. Lastly, collybistin has a pleckstrin homology (PH) domain, which binds phosphoinositides, such as phosphatidylinositol 3-phosphate (PI3P/PtdIns3P) and phosphatidylinositol 4-monophosphate (PI4P /PtdIns4P). PI3P located in early/sorting endosomes has recently been shown to regulate the postsynaptic clustering of gephyrin and GABA-A receptors and consequently the strength of inhibitory synapses in cultured hippocampal neurons. This process is disrupted by mutations in the collybistin gene (ARHGEF9), which cause X-linked intellectual disability (XLID) by a variety of mechanisms converging on disrupted gephyrin and GABA-A receptor clustering at central synapses. Here we report a novel missense mutation (chrX:62875607C>T, p.R356Q) in ARHGEF9 that affects one of the two paired arginine residues in the PH domain that were predicted to be vital for binding phosphoinositides. Functional assays revealed that recombinant collybistin CB3SH3-R356Q was deficient in PI3P binding and was not able to translocate EGFP-gephyrin to submembrane microaggregates in an in vitro clustering assay. Expression of the PI3P-binding mutants CB3SH3-R356Q and CB3SH3-R356N/R357N in cultured hippocampal neurones revealed that the mutant proteins did not accumulate at inhibitory synapses, but instead resulted in a clear decrease in the overall number of synaptic gephyrin clusters compared to controls. Molecular dynamics simulations suggest that the p.R356Q substitution influences PI3P binding by altering the range of structural conformations adopted by collybistin. Taken together, these results suggest that the p.R356Q mutation in ARHGEF9 is the underlying cause of XLID in the probands, disrupting gephyrin clustering at inhibitory GABAergic synapses via loss of collybistin PH domain phosphoinositide binding.